Wards of Hanoi - Koh, David W. H. (David Wee Hock) (Book collections on Project MUSE., 2006)
Analyses state-society interaction at the ward level of Hanoi and shows that at that level the mediation space results from the inefficient party-state as well as from the social dimensions that party-state officials operate when they try to enforce the rule of the one party-state.